PHYSICAL EDUCATION IN HIGH SCHOOL "ENTER" IN THE ENTRANCE EXAM: IMPROVING KNOWLEDGE (Fiep Bulletin - online, 2016)
The physical education at school is a curricular component contemplated in the area of languages, Codes and their technologies and began to integrate the issues of national EXAME NACIONAL DO ENSINO MÉDIO – ENEM and in the entrance exam of Universidade Estadual Paulista UNESP; its expertise on the move in corporal practices are required in questions that involve the field of competences and skills. The scope of this paper is to present and discuss the evidence of issues related to curriculum component physical education in ENEM and evidence of other entrance exam. Cultural society in general understands that these lessons is the time to play, play and train the physical, as in other matters are "studying" is common and often the phrase when referring to the curricular component physical education: - What did you do in class physical education? What threw joked ...? What did you play ...? The challenge for the physical education teacher in high school will develop contextualized classes with the school knowledge and that allow the student to acquire knowledge to continue in the studies and for the community in general recognition of "study" physical education.
Keywords: .